MiR-770-5p facilitates podocyte apoptosis and inflammation in diabetic nephropathy by targeting TIMP3. Issue 4 (29th April 2020) - Wang, Li; Li, Hua
Abstract: Objective: Diabetic nephropathy (DN) is one of the most severe and frequent diabetic complications. MicroRNAs (miRNAs) have been reported to play a vital role in DN pathogenesis. The present study aimed to investigate the molecular mechanism of miR-770-5p in DN. Methods: Podocyte injury model was established by treating mouse podocytes with high glucose (HG, 33 mM) for 24 h. The levels of miR-770-5p and TIMP3 were examined in kidney tissues and podocytes using quantitative real-time PCR (qRT-PCR). Flow cytometry analysis was applied to detect apoptosis in podocytes. Western blot assay was used to measure the protein levels of B-cell lymphoma 2 (Bcl-2), Bcl-2 associated X (Bax) and tissue inhibitors of metalloproteinase 3 (TIMP3). Enzyme-linked immunosorbent assay (ELISA) was conducted to measure the levels of inflammatory factors. The interaction between miR-770-5p and TIMP3 was determined by MicroT-CDS and luciferase reporter assay. Results: MiR-770-5p was up-regulated and TIMP3 was down-regulated in DN kidney tissues and HG-stimulated podocytes. Depletion of miR-770-5p suppressed cell apoptosis and the release of pro-inflammatory factors in HG-treated podocytes. Additionally, TIMP3 was a target of miR-770-5p in HG-treated podocytes. TIMP3 inhibited cell apoptosis and inflammation in HG-treated podocytes. Moreover, TIMP3 knockdown alleviated the inhibitory effect of miR-770-5p silencing on podocyte apoptosis and inflammatory response. Conclusion: Knockdown of miR-770-5p suppressed podocyte apoptosis and inflammatory response by targeting TIMP3 in HG-treated podocytes, indicating that miR-770-5p may be a potential therapeutic target for DN therapy.